Chemisorption on semiconductors: the role of quantum corrections on the space charge regions in multiple dimensions - Ciucci, Francesco; Lee, Sara (Applied physics letters, 2012)
The chemisorption of O2 on nanoscale n-doped CdS semiconductors is computed in terms of a Wolkenstein isotherm coupled to the Schrödinger Poisson equation. Present numerical results show the dependence of the chemisorbed charge and the differential capacitance on oxygen partial pressure. A comparison against the classical Poisson-Boltzmann approach shows a higher chemisorbed charge in the quantum model, but a greater differential capacitance in the classical case.